Frequency of live Births in Patients with Unexplained Recurrent Abortions Treated with low Molecular Weight Heparin and Aspirin (Medical Forum Monthly, 2024)
Objective: To determine the frequency of live birth in patients with unexplained recurrent abortions treated with low molecular weight heparin and aspirin.Study Design: Descriptive studyPlace and Duration of Study: This study was carried out at Department of Obstetrics & Gynaecology, Unit-III, Nishtar Medical College & Hospital, Multan from 01.01.2014 to 31.12.2014.Materials and Methods: Sixty women with past history of two or more previous unexplained recurrent abortions who received low-molecular weight heparin (LMWH) and low dose aspirin (LDA) were included in the study and followed subsequently for the pregnancy outcome in the form of live birth measure.Results: The age range between 20 to 40 years with mean 32.38±3.64 years. A total of sixty patients were studied with a 58.3% patients were belong to age group of 31-35 years. Previous abortion percentage was 36.7% with 2 abortions while 63.3% with 3 abortions with mean 2.63±0.49 abortions. Live birth was recorded in 51 out of 60 patients with percentage of 85%.Conclusion: An enhancement in the live-birth rate was observed after low-molecular weight heparin (LMWH) and low dose aspirin (LDA) administration, in patient with 2 or more consecutive unexplained recurrent abortions.